Guideline update: The British Thoracic Society Guidelines on home oxygen use in adults. Issue 6 (27th April 2015) - Hardinge, Maxine; Suntharalingam, Jay; Wilkinson, Tom
Abstract : The 2015 British Thoracic Society (BTS) Home Oxygen Guidelines provides detailed evidence-based guidance for the use of oxygen by patients in their own homes or other non-acute hospital settings.